Pluralisme Agama Perspektif Abdul Karim Soroush: Kajian Teoritis dan Filosofis - Faza 'Ainun Najah; Hakam Al-Ma’mun (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Pluralism, in the context of religion, on the one hand is an established term that is understood as a necessity that cannot be denied, but on the other hand, pluralism seems full of misunderstandings because it assumes that all beliefs are true. This debate will not seem to meet a common ground because human thoughts continue to develop and clash with each other. A modern reformist Islamic figure, Abdulkarim Soroush, comes up with arguments that support the spirit of pluralism. His thoughts are interesting because they often contradict other Muslim figures in Iran. This study aims to explore deeply the values ​​of religious pluralism from a figure who is labeled a "liberal Muslim intellectual". This study will then look for its relevance to the context of religious plurality in Indonesia by formulating the components of the formation of a pluralist society resulting from Soroush's idea. His scientific background and the complexity of the Iranian conflict, as the country where he spent most of his life, were taken into consideration by researchers in choosing this character. These two factors are considered to have a major influence on Abdulkarim Soroush's thought process. The results of this study indicate that religious pluralism according to Soroush is a sunnatullah that must exist in the world, therefore every human being must have the spirit to uphold religious pluralism. Indonesia also has components of a pluralist society based on Soroush's arguments. Keywords: pluralism, religious pluralism, Abdulkarim Soroush, Sunnatullah, Indonesia